2001
DOI: 10.1007/s002280100366
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute renal colic in a French emergency department: a comparison of simulated cases and real cases in acute pain assessment and management

Abstract: These results show a clear difference between intention to treat and real prescriptions for patients suffering from acute renal colic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A study comparing prescription intentions and actual prescriptions in a sample of practitioners showed that their real prescriptions are more inadequate than their intentions to treat. 11…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing prescription intentions and actual prescriptions in a sample of practitioners showed that their real prescriptions are more inadequate than their intentions to treat. 11…”
Section: Discussionmentioning
confidence: 99%
“…The under-use of paracetamol in unrelieved patients can be incriminated, but, due to its slower onset of action, this factor does not seem likely to be preponderant in the pre-hospital setting. These results suggest that implementation of therapeutic protocols are not sufficient to improve quality of care, and that repeated evaluation must be done to identify non-compliance and build good habits (38,39). To improve pain relief in the field, emergency teams should consider the association of non-narcotic analgesics along with a titration protocol for morphine.…”
mentioning
confidence: 96%